Corporate reputation: A definitional landscape - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2014)
Corporate reputation in recent times has continued to become very important in business and it, today, plays more decisive role in sustaining the growing presence of organizations in their many markets in terms of their future survival. The reputation of a company is shaped, developed or lost during its operations in its community and market. The reputation of a corporate entity, affects that entity's activities and many other organizations it interacts with. Therefore, to gain a sustainable reputation over time and avoid the loss of reputation, maintaining good reputation should be considered as an important factor which will contribute to the organisation's value creation ability. In contrast to the popular belief, any of loss of reputation by an entity will not be easy to gain back or compensate for. This study presents a discussion of corporate reputation, fundamental concepts that are found in the literature and the rising importance of reputation in today's corporate changing environment. © Springer-Verlag Berlin Heidelberg 2014. All rights are reserved.